Comparing Price Levels of Hospital Services Across Countries Results of Pilot Study - Koechlin, Francette (OECD Health Working Papers, 2010)
Health services account for a large and increasing share of production and expenditure in OECD countries but there are also noticeable differences between countries in expenditure per capita. Whether such differences are due to more services consumed in some countries than in others or whether they reflect differences in the price of services is a question of significant policy relevance. Yet, cross-country comparisons of the price of health services are rare and fraught with measurement issues. This paper presents a new set of comparative prices for hospital services in a selection of OECD countries. The data is novel in that it reflects quasi-prices (negotiated or administrative prices or tariffs) of the output of hospital services. Traditionally, prices of outputs have been compared by comparing prices of inputs such as wage rates of medical personnel. The new methodology moves away from the input perspective towards an output perspective. This should allow productivity differences between countries to be captured and paves the way for more meaningful comparisons of the volume of health services provided to consumers in the different countries. One of the key findings of the pilot study is that the price level of hospital services in the United States is more than 60 % above that of the average price level of 12 countries included in the study. Price levels turn out to be significantly below average in Korea, Israel and Slovenia